Financial market integration and international capital flows - Irwin, G (Elgar, 2001)
Eighteen previously published papers consider the lessons to be learned from the financial and currency market crises of the 1990s and how the international financial system should be reformed to harness the benefits of financial liberalization and capital mobility, without destabilizing the international financial system. Papers examine whether, in recent years, international capital flows have been excessively volatile and a source of instability; consider proposals for placing restrictions on capital flows; study the Mexican crisis of 1994-95 and the East Asian crisis of 1997-98; and draw lessons from the experience of the 1990s, including policy implications for governments, regulators, and the relevant international organizations. Irwin is at University College, University of Oxford. Vines is at Balliol College, University of Oxford, at CEPR, and at Australian National University. Name index.